Medición e impacto de la actividad económica informal en el ámbito tributario en la ciudad de Guayaquil - Parra Rosero, Alex (2011)
Present research is related to a study about the measuring and impact of economical informal activity in the tax system field. Drastic transformations related to the economical instability are watched. Diagnoses done are product of statistics and economical analysis and study which were prepared efficiently in a field work with the assistance of students and teachers of the UPS.